2015
DOI: 10.1016/j.chroma.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate monolith chromatography as a tool for waterborne virus removal

Abstract: Enteric viruses are commonly present in environmental waters and represent the major cause of waterborne infections and outbreaks. Since traditional wastewater treatments fail to remove enteric viruses in the water purification process, they are released daily into environmental waters. Monolithic supports have enabled chromatography to enter the field of virology. They have been successfully used in virus purification and concentration. In this work quaternary amine (QA) methacrylate monoliths were exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Coupling columns with orthogonal retention mechanisms in-tandem (hydrophobic and anion exchange) removed interferences to the anion exchange mode, decreased the pressure build-up along the loading step, and enhanced the columns' lifetime [71]. Coupling orthogonal retention chemistries in MAF is possible, but this feature still is to be experimentally demonstrated.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupling columns with orthogonal retention mechanisms in-tandem (hydrophobic and anion exchange) removed interferences to the anion exchange mode, decreased the pressure build-up along the loading step, and enhanced the columns' lifetime [71]. Coupling orthogonal retention chemistries in MAF is possible, but this feature still is to be experimentally demonstrated.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Even with the large flow-through pores of MAF (15-20 μm), the flow rate had to be limited to 0.57 L/min to prevent clogging [65]. The methacrylatebased methods adopted the 0.8 μm pre-filter to exclude bacteria and suspended matter that clogs the monoliths and demands lower flow rates to process large sample volumes [31,71].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Such efficient binding of enteric viruses to monoliths has been exploited in an up‐side‐down achievement to actually purify wastewater treatment plant effluent from five waterborne enteric viruses . Following optimization using analytical discs, a large (8 mL) methacrylate column was used as a valuable tool for simultaneous removal of different viruses from a large quantity of contaminated water.…”
Section: Preconcentration Contributing To a More Sensitive Detectionmentioning
confidence: 99%
“…Rački et al [152] reported the removal of viruses from a wastewater sample using a methacrylate monolith functionalized with quaternary amine moieties. Purification of the water samples from the 5 enteric viruses tested was achieved to a level where the viruses were not detected using Real Time-quantitative Polymerase Chain Reaction (RT-qPCR).…”
Section: Applications Of Methacrylate Polymer Monoliths In Separatmentioning
confidence: 99%